Field test and numerical simulation of ground settlement in super shallow buried station excavation supported by transverse pipe roof - Wang, Jun; Li, Xun; Wu, Shengzhi; He, Zhiwei; Wei, Yuanjin (Frontiers in Earth Science, 2023)
The pipe roof is an effective means to control the surface settlement during the construction of the super-shallow buried subway station. The transverse pipe roof method can not only reduce the construction work surface, but also improve the construction efficiency by multi-stage flow construction.Based on the transfer station project of the Olympic Sports Center of Jinan Rail Transit Line 3, the ground settlement law caused by the excavation of ultra-shallow buried subway station under the action of transverse pipe roof is analyzed through field measurement. The mechanism of pipe roof controlling ground settlement and the influence of steel pipe spacing and steel pipe length on the bearing mechanism of pipe roof are analyzed by numerical simulation. The following conclusions are drawn. (1) The surface settlement curve caused by the excavation of the small pilot tunnel in the lateral direction of the station is a wavy U-shaped, and the surface settlement curve becomes a smooth U-shaped after the soil is broken. In the longitudinal direction of the station, the surface settlement is jagged, and the surface settlement above the pipe roof is less than the surface settlement between the pipe roofs. (2) After soil excavation, pipe roof can bear the load of surrounding rock and restrain the settlement of soil above, and soil arch effect is formed between pipes to restrain the relaxation of soil between pipes. With the increase of the spacing of the steel pipe, the height of the soil arch increases. After exceeding a certain spacing, the micro-soil arching effect disappears and the surface settlement increases. (3) The length and stiffness of pipe roof will affect the bearing capacity of pipe roof and there is an upper limit. When it exceeds the upper limit, increasing the length or stiffness of pipe roof has little effect on the control effect of ground settlement. The research can provide reference for shallow buried excavation station and other projects.